METHODOLOGICAL PARTICULARITIES IN INVESTIGATING HOME LARCENY - NICOLETA-ELENA BUZATU (Challenges of the Knowledge Society)
The study below is meant to focus on the methodological particularities regarding the investigations concerning home larcenies. In the Romanian penal law, the simple or the aggravated theft as well as the other infringements against patrimony are charged by the special part of the penal Code. The theft from dwellings takes the most unexpected and diverse forms: the only main preoccupation of the thieves is not to be seen or caught in the act. Consequently, the main aspects to be analyzed are: establishing the flagrant infringement, investigating the scene of the deed, hearing the injured person, hearing the witnesses, searching, identifying and catching the doers, as well as other activities of penal suing necessary in investigating any home larceny.